EXPERIMENTAL STUDY OF CYCLE LYOPHILIZATION OF ORGANIC NATURAL PRODUCTS - Armijo C., Javier (2008)
In this paper we determine the profiles of temperature cycle of freeze drying of natural organic products, such as lucuma and garlic. The equipment used is a Freeze Dryer RIFICOR model LI-E300-CRT. This has a drying chamber, rectangular shelf, condenser and vacuum pump. The freezing temperature is -35 °C and the temperature of the condenser is -40 ºC, the vacuum pressure is 20 microns Hg.